Hubungan antara Dukungan Dengan Beban Keluarga untuk Mengikuti Regimen Terapeutik Klien Halusinasi di Rumah Sakit Jiwa Daerah Provinsi Jambi - Isti Harkomah; Desi Anmi Putri (HB PRESS, 2021)
Hallucinations are one of the symptoms often found in clients with mental disorders. The family has the responsibility to care for it, but it causes a burden on the family in the implementation. The various impacts faced by the family as a family burden will affect family behavior in caring for hallucinations, including how to support compliance to treatment or therapeutic regimens, and thereby the family support is needed. This study aimed to determine the association between family support and family burdens for following the therapeutic regimen of hallucination clients at the Regional Mental Hospital in Jambi Province. This study used a cross-sectional design. The population in this study were all clients with hallucinations that visited the polyclinic in 2019 (132 people). A total of 56 people were selected using an accidental sampling method. The data were collected using a questionnaire sheet, and the study results were analyzed by univariate and bivariate analyses. The results of the univariate analysis showed that 30 respondents (53,6%) had good family support while 29 respondents (51,8%) had a family burden in the poor category in following the therapeutic regimen of hallucination clients at the Regional Mental Hospital in Jambi Province. The bivariate analysis results showed a significant association (p=0,000) between family support and family burdens in following the therapeutic regimen for hallucination clients at the Regional Mental Hospital in Jambi Province.